Retention of dental practitioners in rural health services in Iran: Experiences from Kerman province - Mohammadreza Amiresmaili; Majid Heidari Jamebozorgi; Azam Heidari Jamebozorgi; Morteza Arab-Zozani (Dental Research Journal, 2022)
Background: In Iran, the inequitable distribution of health-care staff, especially dental practitioners between rural and urban areas has a major impact on the delivery of care for those living in rural communities. This study investigated the factors affecting the retention of dental practitioners to stay in the rural areas. Materials and Methods: This is a cross-sectional study conducted in 2019. All dental practitioners working in health services centers covering a population lower than 20,000 people in Kerman province participated in this study (n = 81). A researcher-designed questionnaire was used for the data collection. The data were analyzed using the descriptive statistics and logistic regression through the SPSS software. Results: The mean age of the participants was 29.2 ± 6.5 and 39.5% were female. The results showed that about two-thirds of native dentists (with local origin), 73.3% of married dentists, and all dental practitioners who had no children or had a child under the age of six were willing to continue working with their current Comprehensive centers of health services compared to other dentists. Univariate and multivariate logistic regression showed that there was a significant relationship among dentists' age, monthly salary, and facilities available in the area (place of residence, availability of vehicles, etc.), view of dental practitioners on living in a rural area, and view of dentists' families on living and working in the area (p < 0.05). Conclusion: More than half of the dental practitioners declared their willingness to stay in rural areas, although, in practice, this amount of presence in rural areas does not meet the needs of residents. Financial issues, amenities, and facilities in the rural areas can have a positive impact on the retention of dental practitioners.